The Effect of Democratic Leadership Style, Work Motivation, and Communication on Employee Morale at CV Gardatama Toyoresmi Ngasem Kediri - Tangga, Davis Harya; Ambarwati, Diana; Saptaria, Lina (Business and Investment Review, 2023)
This study aims to determine the effect of democratic leadership style, work motivation and communication on employee morale at CV Gardatama Toyoresmi Ngasem Kediri. The analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression analysis, T test, F test. The population in this study were all 40 employees and the sample used was 40 respondents because it used saturated samples. The results of research on CV Gardatama Toyoresmi Ngasem Kediri show that the variables of democratic leadership style (X1), motivation (X2), and communication (X3) jointly affect the work spirit variable (Y). This can be proven from the Sig value of 0.000 <0.05.